The influence of financial decentralization on the restoration of the economy of Donbas - Fomichenko, I.; Barkova, S. (Економічний вісник Донбасу, 2018)
The article deals with the specifics of Donbas regional development from the point of view of the introduction of decentralization processes in a situation of armed conflict and a high degree of political and socioeconomic uncertainty. The features of the formation of local budgets of Donetsk region are determined. The proposed improvement of the policy of intergovernmental transfers of security of the eastern region, which involves the development of strategic documents of socio-economic development by each united territorial community. У статті розглянуто специфіку регіонального розвитку Донбасу з позицій впровадження децентралізаційних процесів в умовах збройного конфлікту і високого ступеня політичної та соціально-економічної невизначеності. Встановлено особливості формування місцевих бюджетів Донецької області. Запропоновано удосконалення політики міжбюджетних трансфертів забезпеченості східного регіону, що передбачає розробку стратегічних документів соціально-економічного розвитку кожною об’єднаною територіальною громадою. В статье рассмотрена специфика регионального развития Донбасса с позиций внедрения децентрализационных процессов в условиях вооруженного конфликта и высокой степени политической и социально-экономической неопределенности. Установлены особенности формирования местных бюджетов Донецкой области. Предложено усовершенствование политики межбюджетных трансфертов обеспеченности восточного региона, которая предусматривает разработку стратегических документов социально-экономического развития каждой объединенной территориальной общиной.